Multidrug-Resistant Tuberculosis in Alberta and British Columbia, 1989 to 1998. Issue 2 (3rd April 1999) - Hersi, Ahmed; Elwood, Kevin; Cowie, Robert; Kunimoto, Dennis; Long, Richard
Abstract : OBJECTIVE: To describe the extent of the problem of multidrug-resistant tuberculosis (MDR-TB) in Alberta and British Columbia from 1989 to 1998. DESIGN: A retrospective, population-based descriptive study of all notified MDR-TB cases in the context of all notified TB cases, all notified culture-positive TB cases and all notified drug-resistant TB cases. SETTING: Provinces of Alberta and British Columbia, and their TB registries. PATIENTS: All people with TB reported to the TB registries of Alberta and British Columbia between January 1, 1989 and June 30, 1998. MAIN OUTCOME MEASURES: Drug susceptibility testing was performed in all cases of culture-positive TB. Demographic, clinical and laboratory data on all cases of MDR-TB were recorded. RESULTS: Of 4606 notified cases of TB, 3553 (77.1%) were culture positive. Of these, 365 (10.3%) were drug resistant; of the drug-resistant cases, 24 (6.6%) were MDR. Most MDR-TB patients were foreign-born; of the four Canadian-born patients, two were infected while travelling abroad. Although foreign-born patients were significantly more likely to harbour drug-resistant strains, 14.3% versus 4.8%, respectively (P<0.001), among those who were harbouring a drug-resistant strain, the proportion of Canadian-born versus foreign-born patients with an MDR strain was the same (6.7% versus 6.6%, respectively). From 1994 to 1998 versus 1989 to 1993, the proportion of all drug-resistant strains that were MDR was greater (9.0% versus 4.3%, respectively), but the difference was not statistically significant. Isolates from 16 of the 24 MDR-TB cases had been archived. Each of these was fingerprinted and found to be unique. Most MDR-TB cases (88%) were respiratory. Of those tested for human immunodeficiency virus (n=17), only one was seropositive. MDR-TB was 'acquired' in 67% and 'primary' in 33% of cases. Eight (33%) of the MDR-TB cases received curative courses of treatment, six (25%) are still being treated, and the remainder have either died (five, 21%), transferred out (four, 17%) or become 'chronic' (one, 4%). No secondary case of MDR-TB has been identified in Alberta and British Columbia. CONCLUSIONS: Most MDR-TB in Alberta and British Columbia is imported. The proportion of all drug-resistant cases that are MDR appears to be increasing, but not because of disease acquired from recent contact with MDR-TB in Canada.